Performance evaluation of the PET component of a sequential APD-based micro-PET/MR imaging system. (5th May 2017) - Vrigneaud, J M; Walker, P; Barbier, B; Camacho, A; Oudot, A; Collin, B; Brunotte, F
Abstract: The LabPET/MR imaging system is a new preclinical prototype with sequentially-acquired PET/MR scan capabilities. The dual modality system is composed of a modified APD-based LabPET4 subsystem, coupled with a cryogen-free superconducting 3.0 T MRI subsystem. The objective of the study was to characterize the imaging performance of the PET subsystem and identify the change in PET performance due to the presence of the magnetic field. NEMA NU-4-2008 performance characteristics were conducted with the MR subsystem switched ON and OFF. Influence of the temperature was also investigated by repeating selected performance tests. In the ON configuration, the radial/tangential FBP spatial resolution ranged from 1.62 ± 0.08/1.88 ± 0.08 mm to 2.83 ± 0.11/2.03 ± 0.03 mm at the axial center field of view. The peak absolute sensitivity for an energy window of 250–650 keV was 0.87%. The maximum noise equivalent counting rates were 133 kcps at 3.8 MBq ml −1 and 25 kcps at 0.4 MBq ml −1 for the mouse- and rat- like phantoms, respectively. The corresponding scatter fractions were 13% and 23%. No differences could be identified between the ON and OFF configuration, except for a mean loss in peak absolute sensitivity of 5.1 ± 0.5% which was attributed to a mean rise in temperature of 1.2 °C when the magnet was ON. Compared with the LabPET standalone scanner, the LabPET/MR imaging prototype is working in a warmer environment and this impacts on the sensitivity of the APD-based LabPET scanner.